PENGARUH ANALISIS JABATAN DAN ANALISIS PEKERJAAN TERHADAP KINERJA GURU SMP/MTS KECAMATAN LAMPIHONG KABUPATEN BALANGAN - Jamil Rifani (UPT Publikasi Dan Pengelolaan Jurnal Universitas Islam Kalimantan MAB Banjarmasin, 2019)
This study aims to determine the partial effect of job analysis and job analysis on the performance of SMP / MTs teachers in Lampihong District, Balangan Regency. The study sample numbered 85 people with a Porpusive Sampling technique ie the sample determined by researchers outside the informant was <25% of all SMP / MTs teachers in Lampihong Subdistrict, Balangan Regency. The results of this study are (1) there is a significant influence between job analysis on the performance of SMP / MTs teachers in Lampihong Subdistrict Balangan Regency (t-count> t-table value = 3,223> 1,890); there is a significant influence between job analysis on the performance of SMP / MTs teachers in Lampihong Subdistrict, Balangan Regency (t-count> t-table value = 3,269> 1,890); (3) job analysis and job analysis simultaneously affect the performance of teachers in the SMP / MTs of Lampihong Sub-district of Balangan Regency (f-count> f-table value = 18.098> 4.95); (4) job analysis has a dominant influence on teacher performance compared to job analysis (tcount job analysis = 3,269, tcount job analysis = 3,223).